2012
DOI: 10.1007/s10517-012-1888-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Functions of Erythrocyte Membranes in Pregnant Women after Exacerbation of Herpesvirus Infection

Abstract: Herpesvirus infection is associated with an increase of LPO and of the membrane lipid and lipid-protein layers microviscosity in erythrocyte membranes of pregnant patients. This results in modification of the erythrocyte stromal protein composition. Erythrocyte deformability increases sharply under these conditions, this leading to disorders in tissue metabolism in the organs of pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…If the volume of erythrocyte is large, then there are not enough surfaces for it to change its shape and pass into the microcirculatory pathway. [10][11][12] The studies of recent years have shown that in the process of adaptation, primarily, the properties of erythrocytes have the ability to deform. [10,[12][13][14] Proceeding from this, we studied the possibility of changing the shape of red blood cells in the process of adaptation to different light status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the volume of erythrocyte is large, then there are not enough surfaces for it to change its shape and pass into the microcirculatory pathway. [10][11][12] The studies of recent years have shown that in the process of adaptation, primarily, the properties of erythrocytes have the ability to deform. [10,[12][13][14] Proceeding from this, we studied the possibility of changing the shape of red blood cells in the process of adaptation to different light status.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] The studies of recent years have shown that in the process of adaptation, primarily, the properties of erythrocytes have the ability to deform. [10,[12][13][14] Proceeding from this, we studied the possibility of changing the shape of red blood cells in the process of adaptation to different light status. Table 2 shows the dynamics of deformability index of erythrocytes in the blood of chickens under adaption to light status [ Figure 1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В организме беременных в условиях цитомегаловирусной инфекции (ЦМВИ) возникают неспецифические метаболические расстройства в виде активации процессов пероксидации липидов с накоплением свободно-радикальных продуктов, повреждающих мембрану эритроцита [3], что приводит к перераспределению электронов на мембране, вызывает конформационные изменения белков цитоскелета, гемоглобина и метаболических ферментов, изменяет диффузионные свойства мембраны. В результате происходит нарушение функциональных особенностей эритроцитов как резервуара для переноса кислородных молекул и углекислого газа в фетоплацентарной системе, что ведет к возникновению гипоксического состояния, которое осложняет течение беременности и внутриутробного развития плода [4,5].…”
Section: The Role Of Eicosapentaenoic Acid and Superoxideunclassified
“…Определяется высокое содержание циркулирующих эндотелиальных клеток, что является признаком дисфункции эндотелия [29]. Как было показано в ряде исследований [19,55] анемия у беременных сопровождается формированием оксидативного стресса [24], а длительная терапия препаратами железа, как правило, способствует образованию активных форм кислорода и нарушению функции клеток эндотелия. Дисфункция эндотелия, в свою очередь, является причиной синдрома неадекватной продукции эритропоэтина на гипоксию и, таким образом, усугубляет течение анемии и является предиктором гестоза [14,55], неблагоприятных исходов беременности и более высоко риска развития сердечно-сосудистых заболеваний в дальнейшей жизни [52].…”
Section: эндотелий при физиологической и патологически протекающей беременностиunclassified